2019
DOI: 10.1007/s00464-019-07258-z
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous computer-assisted assessment of mucosal and serosal perfusion in a model of segmental colonic ischemia

Abstract: Background Fluorescence-based enhanced reality (FLER) enables the quantification of fluorescence signal dynamics, which can be superimposed onto real-time laparoscopic images by using a virtual perfusion cartogram. The current practice of perfusion assessment relies on visualizing the bowel serosa. The aim of this experimental study was to quantify potential differences in mucosal and serosal perfusion levels in an ischemic colon segment. Methods An ischemic colon segment was created in 12 pigs. Simultaneous q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…As a result, serosal perfusion only can be quantified. It has been previously shown that the ischemia behavior within the gastrointestinal tract varies when comparing the serosal with the mucosal side [ 14 ]. Confocal laser endomicroscopy (CLE) is a high-resolution microscopic optical imaging modality, which allows for a detailed morphological assessment of the gastrointestinal mucosa.…”
mentioning
confidence: 99%
“…As a result, serosal perfusion only can be quantified. It has been previously shown that the ischemia behavior within the gastrointestinal tract varies when comparing the serosal with the mucosal side [ 14 ]. Confocal laser endomicroscopy (CLE) is a high-resolution microscopic optical imaging modality, which allows for a detailed morphological assessment of the gastrointestinal mucosa.…”
mentioning
confidence: 99%
“…weight 42⋅8(3⋅9) kg) were used in the study, as part of the ELIOS (Endoscopic Luminescent Imaging for precision Oncologic Surgery) protocol, which received full approval from the local Ethical Committee on Animal Experimentation (ICOMETH 38.2017.01.085), and the Ministry of Superior Education and Research (APAFIS 8721-2017013010316298v2). All animals used in the experimental laboratory were managed according to French laws for animal use and care, European Community Council directives (2010/63/EU), and ARRIVE guidelines, as described previously 11 .…”
Section: Methodsmentioning
confidence: 99%
“…Focusing on the 40‐s time interval between FSI arrival and signal decrease, the variation from 25 to 75 per cent of maximal intensity was analysed. This slope of FSI evolution dynamics was used for quantitative near‐infrared fluorescence perfusion imaging 11,12 . Perfusion data from each imaging system were translated into a colour‐coded cartogram, which was superimposed on to the real‐time view of the corresponding left and right camera systems 12 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 They report that metrics from this simple semiquantitative approach performed well diagnostically to identify viable and nonviable small bowel in rats. Diana et al [30][31][32][33] developed a fluorescence-based enhanced reality approach that uses time-to-peak (TTP) analysis to produce a perfusion-like map that is overlaid onto the surgeon's view of the field and evaluated the approach in a variety of pig models. Similar TTP methods have also been evaluated in human patients.…”
Section: Introductionmentioning
confidence: 99%